Modified Water Displacement Method and its Use for Determination of Bulk Density of Porous Materials - Robert, Ubong Williams; Etuk, Sunday Edet; Agbasi, Okechukwu Ebuka (UIR PRESS, 2019)
In this research work, a modified water displacement method (MWDM) was designed and used in addition to geometry method (GM) to measure the bulk volume and then determine the bulk density values of asbestos ceiling board, cardboard paper, chalk, clay (compacted) and gypsum board that have been sun-dried to constant weight. The mean bulk densities determined by both methods were compared with the reference bulk density values of the same porous materials obtained in this work using standard test procedure in accordance with ASTM D6683-14. It was observed that, for all the tested porous materials, the percentage error in the mean bulk density values ranged from 2.3% to 49.6% when using GM and 0.9% to 5.7% by using the MWDM. Also, at 0.05 level of significance with a degree of freedom of 3, correlation coefficients of 0.7430 and 0.9955 were obtained in the cases of GM and the MWDM respectively. Again, all other analyses performed similarly revealed that the mean bulk densities obtained by the MWDM only were in close agreement with their corresponding reference values, thereby implying that apart from being cost-effective, the MWDM is better than GM in terms of accuracy, reliability, and validity. More importantly, it is noteworthy that even if the glass cylinder available for use is ungraduated, this MWDM can be employed to obtain accurate, reliable and valid bulk density values of porous materials in order to enhance thorough physical characterization, proper selection and suitable applications of such materials.